Estudo da força de adesão de tortas de filtração de gases em diferentes condições operacionais - Barros, Priscila Martins de (Universidade Federal de São Carlos, 2010)
Gas filtration is one of the most important methods used in gas-solid separation. During a filtration process, a gas containing an amount of solid particles passes through a porous filter medium which retains the particles. Particles are deposited throughout the filtration process forming a porous cake. The resistance to gas flow through the filter increases when the filtration cake is formed, which makes pressure drop increase. Once pressure drop is considered relatively high, the cake must be removed with cleaning processes in order to minimize resistance to gas flow and, consequently minimize operational cost. Thus, cake removal enhancements might represent important earnings, besides contributing to filtration process improvements. Therefore, this study had the objective of investigating the behavior of gas filtration cake removal from filter media through the determination of adhesion force per unit area in different operational conditions. This parameter is very important during dust cake removal, once it makes it possible to propose the best operational conditions for a more efficient removal. In this work, two types of particulate matter, phosphate concentrate and manioc starch, and three types of filter media, polypropylene, acrylic and polyester, were studied. Three superficial filtration velocities (5; 7.5 and 10 cm/s) and five different amounts of powder deposited on the filter medium, which respectively correspond to 0.039; 0.055; 0.064; 0.071 and 0.088g/cm2, were also examined. The dust cakes removal was performed by using the reverse air flow method, being the dust cakes submitted to various successive cleaning velocities. Therefore, each filter medium was cleaned at a lower velocity and, immediately afterwards, at a higher velocity, going through the following cleaning velocities 0.5; 1; 2; 3; 6; 9; 12 and 15 cm/s. Thus, a value of pressure drop was obtained for each cleaning velocity. The adhesion force per unit area was acquired with the method proposed by Seville et al. (1989). From the results obtained, it was verified that the values of adhesion force per unit area found were not influenced by the amount of powder deposited per unit area; the experimental data fit a single curve; the phosphate concentrate presented higher values of adhesion force per unit area when compared to the manioc starch; adhesion force values increased with the increase in gas superficial filtration velocity for both phosphate concentrate and manioc starch; the polypropylene felt presented the highest removal tension values followed by the acrylic and polyester felts; and that the higher the removal tension values the lower the values obtained for the effective separation distance between particles.
Keywords: Filtração de gases; Tortas de filtração de gases; Força de adesão; ENGENHARIAS::ENGENHARIA QUIMICA